Six assertions about the salutogenic approach and health promotion (Italian Journal of Public Health, 2010)
Background: The concept of health is a continuously changing issue, with ever richer and more comprehensive meanings and definitions. In recent decades, we have witnessed a strong evolution of the scientific paradigms and cultural frameworks that influence health patterns. In particular, in 1986 the Charter of Ottawa gave further dimensions to the concept of health and pushed the concept of health promotion to the forefront. In this context, the salutogenic approach, proposed by A. Antonovsky, represents a theoretical contribution which stimulates discussion about meanings and implications.Aim and Methods: The present paper aims to provide a conceptual framework for the interpretation of health patterns and to broaden the theoretical interpretation of the salutogenic approach. In order to do this, a literature review was carried out, taking into account several disciplines and perspectives, including sociology and anthropology. The data collection for this paper was undertaken through two parallel literature reviews and systematisation of the information gathered.Results: The following health patterns were identified: the disease treatment pattern, the health care pattern, the disease prevention pattern and the health promotion pattern. These approaches allow one to better analyse and understand the added values of the salutogenic approach.Conclusions: The present discussion contributes to the debate surrounding the salutogenesis theory and its applicability to the healthcare setting by proposing six assertions about the salutogenic approach to health promotion.
Keywords: Health patterns; salutogenic approach; human potential; health promotion